Impact of seasonality on the prevalence and risk factors of Giardia lamblia infections among the aborigines - Noradilah S.A.; Moktar N.; Lee I.L.; Salleh F.M.; Anuar T.S. (Wolters Kluwer Medknow Publications, 2024)
Indexed by Scopus